Wie häufig betreffen Gegenanzeigen und Warnhinweise in deutschen Fachinformationen pädiatrische Patienten? - Wimmer, Stefan; Rascher, Wolfgang; Neubert, Antje (Klinische Pädiatrie, 2019)
Background 3.2-3.8% of all medicine prescriptions for minor outpatients are off-label only because of the patients' age group. The younger, the more patients are affected by this issue. Only one fifth of the most commonly used medicines for newborns are licensed for this age group. The aim of this study is to analyse all German SmPCs whether they contain contraindications and warnings that specifically concern paediatric patients. Methods All available SmPCs were processed to search the sections Contraindications and Special warnings and precautions for information on paediatric age groups. Results were evaluated for differences between age groups, ATC classification and routes of application. Results 13547 SmPCs (22863 medicinal products) were evaluated. For 3603 (15.8%) medicinal products the SmPC contained contraindications for at least one paediatric age group. For 9687 (42.4%) medicinal products contraindications or warnings were found, including 2833 (12.4%) where all patients below 18 years were affected. Preterms were particularly affected (n=9581, 41.9%) as well as the ATC therapeutic subgroups contrast media (89.0%), cough and cold preparations (86.2%) and Corticosteroids (topical 88.2%, systemic 86.6%). Concerning liquids for oral use the proportion was higher than average (58.2%). Conclusion It can be assumed that for most medicinal products the contraindications for paediatrics result from a lack of data and age specific formulations rather than from pharmacokinetic or -dynamic differences in paediatric patients. The EU Paediatric Regulation did not significantly stimulate the conduction of paediatric studies in off-patent medicines to this day.
CRIS-Team Scopus Importer:2019-07-26
Keywords: Contraindications; Drug safety; Off-Label-Use; Paediatrics; SmPC